Efficient mechanism of DNA repair stabilizes genome of Arabidopsis thaliana from the Chernobyl zone - Shevchenko, G.V.; Talalaiev, O.S. (Доповіді НАН України, 2017)
Tolerance to radiomimetics and heavy metals has been investigated in Arabidopsis thaliana plants collected in the Chernobyl zone. Decrease of root growth and DNA damage level of a single cell have been evaluated. Tolerance of A. thaliana from the zone to the growth on genotoxic medium has been revealed. It is noted that certain Arabidopsis plants recover genomic DNA faster than control ones collected outside of the zone. Screening revealed plant lines expressing various levels of tolerance to genotoxins.